Analysis of the Effect of Justice, Perceived Organizational Support on Performance with Employee Engagement as Intervening Variable at PT. Brantas Abipraya - Hartono, Muhamad Arif; Riwayati, Hedwigis Esti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to investigate the influence of justice on employee engagement, influence of perceived organizational support on employee engagement, influence of justice on performance, influence of perceived organizational support on performance, influence of employee engagement on performance, mediating influence of employee engagement on the relationship between justice and performance, and the mediating influence of employee engagement on the relationship between perceived organizational support and performance. This research employs a quantitative approach by distributing questionnaires to 202 employees of PT Brantas Abipraya using SmartPLS tools. The results of this study indicate that justice has a positive effect on employee engagement, perceived organizational support has a positive effect on employee engagement, justice positively affects performance, perceived organizational support positively affects performance, employee engagement positively affects performance, employee engagement positively mediates the effect of justice on performance, and employee engagement positively mediates the effect of perceived organizational support on performance